PERSEPSI PASANGAN USIA SUBUR TERHADAP PROGRAM KELUARGA BERENCANA (KB) DI DESA SUNGAI KUNING KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Sri Mulyani; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the Sungai Kuning Village Singingi Subdistrict Kuantan Singingi Regency. This Research aims to determine how the characteristics fertile age couple out of it family planning program, how perceptions fertile age couple out of it family planning program and factors which influence fertile age couple out of it family planning program. The tittle of research is “Perceptions Fertile Age Couple about Family Planning Program (Family Planning) At Sungai Kuning Village Singingi Subdistrict Kuantan Singingi Regency”. The samples in this research is using purposive sampling. Total population out of it family planning programs in the 2014 years amount 48 fertile age couple, takeable sampling 24 fertile age couple representatiyely of population. The method used is descriptive quantitative method. Data networking instruments used were observation and interviews.Results of general research conducted, the researchers can say that the characteristics fertile age couple out of it family planning program subjection mean of respondent attain the age 40 years old,the majority of farmers work, have an income 1.000.000-2.000.000 rupiah, elementary education, Islamic religion, the dominant Javanese and have a 4-7 children. Later in the research of perception fertile age couple out of it family planning program is the dominant perception fertile age couple which previously participated infamily planning program 20 fertile age couple with the range of 3-5 years ago, The perception of the religious factor that religion does not allow family planning because it is haraam in Islam religion.then the perception of cultural factors is that the child has a high cultural value as one of the successors of hereditary in the family tree, and the perception of the age factor, namely that fertile age couple entered the age of the elderly and if forced to keep family planningthen his health will deteriorate namely body aches, head dizziness, weight gain and irregular bleeding. As well as factors affecting fertile age couple out of it family planning programisHealth factors, socialization of health workers and the physical environmental factors, namely the delivery of family planning information program, economic factors and factors husband interdiction.Keywords : Perceptions Fertile Age Couple, Out of it Family Planning, Family Planning Program